A Whisper to a Roar - Moses, Ben (United States : Martinez, Amy, 2012)
A Whisper to a Roar tells the stories of courageous democracy activists in five countries around the world – Egypt, Malaysia, Ukraine, Venezuela and Zimbabwe. From student leaders to prime ministers and heads of state, these activists share their compelling personal stories of struggle, past and present, with their countries’ oppressive regimes.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films